2022
DOI: 10.3390/diagnostics12051033
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s Disease Detection from Resting-State EEG Signals Using Common Spatial Pattern, Entropy, and Machine Learning Techniques

Abstract: Parkinson’s disease (PD) is a very common brain abnormality that affects people all over the world. Early detection of such abnormality is critical in clinical diagnosis in order to prevent disease progression. Electroencephalography (EEG) is one of the most important PD diagnostic tools since this disease is linked to the brain. In this study, novel efficient common spatial pattern-based approaches for detecting Parkinson’s disease in two cases, off–medication and on–medication, are proposed. First, the EEG s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 44 publications
1
26
1
Order By: Relevance
“…The present study used the discrete wavelet transform with threshold entropy, sure entropy, or proposed T-Shannon entropy, achieving accuracy scores of 99.72, 99.66, and 99.89%, respectively (see Table 5). These results are superior to the results of 29,34,35 , and close to the result reported in 30 .…”
Section: Results and Disscussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The present study used the discrete wavelet transform with threshold entropy, sure entropy, or proposed T-Shannon entropy, achieving accuracy scores of 99.72, 99.66, and 99.89%, respectively (see Table 5). These results are superior to the results of 29,34,35 , and close to the result reported in 30 .…”
Section: Results and Disscussionsupporting
confidence: 56%
“…Our proposed methods are compared with existing state-of-the-art techniques to assess their effectiveness for off-PD versus HC classification. From the previous studies summarized in Table 1, we focus on studies that used the same dataset 29,30,34,35 . In 29 , first, the Gabor transformation was used to convert the EEG signals to spectrograms.…”
Section: Results and Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another technique that has been common in deep learning classification of PD-EEG data is to use K-fold cross validation to show the robust classification ability. However, Aljalal et al noted that the combination of epoching and cross validation leads to an information leakage between the train and test sets since both sets will include epochs from the same subjects [6]. To highlight the effect of this information leakage, we performed an investigation using the previous approaches, and found that classification metrics may be dramatically exaggerated (by 20% or more) to values that are not representative of the classifier’s true performance on the test set.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies report very high accuracies above 98%. [5 - 12] However, the methods employed in these articles may suffer from the limitation of information-leakage between the training and testing data [6]. This limitation can lead to large overestimation of classification ability on unseen, real-world data.…”
Section: Introductionmentioning
confidence: 99%